Ligand-Specific Regulation of the Endogenous Mu-Opioid Receptor by Chronic Treatment with Mu-Opioid Peptide Agonists. (24th November 2013) - Murányi, Marianna; Cinar, Resat; Kékesi, Orsolya; Birkás, Erika; Fábián, Gabriella; Bozó, Beáta; Zentai, András; Tóth, Géza; Kicsi, Emese Gabriella; Mácsai, Mónika; Dochnal, Roberta; Szabó, Gyula; et al.
Abstract : Since the discovery of the endomorphins (EM), the postulated endogenous peptide agonists of the mu-opioid receptors, several analogues have been synthesized to improve their binding and pharmacological profiles. We have shown previously that a new analogue, cis-1S, 2R -aminocyclohexanecarboxylic acid 2 -endomorphin-2 (ACHC-EM2), had elevated mu-receptor affinity, selectivity, and proteolytic stability over the parent compound. In the present work, we have studied its antinociceptive effects and receptor regulatory processes. ACHC-EM2 displayed a somewhat higher (60%) acute antinociceptive response than the parent peptide, EM2 (45%), which peaked at 10 min after intracerebroventricular (icv) administration in the rat tail-flick test. Analgesic tolerance developed to the antinociceptive effect of ACHC-EM2 upon its repeated icv injection that was complete by a 10-day treatment. This was accompanied by attenuated coupling of mu-sites to G-proteins in subcellular fractions of rat brain. Also, the density of mu-receptors was upregulated by about 40% in the light membrane fraction, with no detectable changes in surface binding. Distinct receptor regulatory processes were noted in subcellular fractions of rat brains made tolerant by the prototypic full mu-agonist peptide, DAMGO, and its chloromethyl ketone derivative, DAMCK. These results are discussed in light of the recently discovered phenomenon, that is, the "so-called biased agonism" or "functional selectivity".